Field training at Farm Unit, UiTM Sarawak, Kota Samarahan Campus / Nurul Huda - Nurul Huda (Universiti Teknologi MARA, Sarawak, 2014)
This industrial report is submitted to report all the task and activities that have been done in the previous industrial practical training. The students are allowed to choose any organization as their industrial training place. The one that I had selected is Mara University of Technology, UiTM Sarawak. In UiTM Sarawak, there are three campuses. They are UiTM Samarahan 1, UiTM Samarahan 2 and UiTM Mukah. In UiTM Sarawak there are 7 Departments exist and also more than 10 Units under the departments.. The place that I had selected is the Farm Unit, in UiTM Samarahan 1.